Awareness of Age-Related Change: Examination of a (Mostly) Unexplored Concept - Diehl, Manfred K. (Oxford University Press, 2010)
This theoretical article discusses the emerging concept of awareness of age-related change (AARC). We propose that a focus on AARC extends the research traditions on subjective age experiences and age identity and that examination of this concept can serve a stimulating role in social gerontology. After defining and contrasting AARC against similar concepts, several reasons for the relevance of this mostly unexplored construct are provided. The sample domains of health and physical functioning, cognitive functioning, and interpersonal relations are used to illustrate the relevance of AARC. Based on this review, we then provide a heuristic framework that describes antecedents, processes, and outcomes related to AARC. Overall, we argue that research on AARC should become an integral part of social gerontological research.